Синергія стандартів якості з цілями сталого розвитку для управляння цифровою трансформацією бізнес-процесів ІТ компаній - Лисенко, Сергій Миколайович (ТОВ "ДКС Центр", 2024)
Цифрова трансформація стала невід’ємною частиною сучасного суспільства, глибоко впливаючи на всі аспекти життя: економічний, соціальний та екологічний. У цій статті досліджується взаємозв’язок цілей сталого розвитку (ЦСР) з урахуванням стандартів якості під час цифрової трансформації бізнес-процесів IT компаній. Аналізується, як впровадження цифрових технологій, таких як Інтернет речей (IoT), блокчейн, штучний інтелект (AI) та хмарні обчислення, сприяє економічному зростанню, знижує вплив на навколишнє середовище та покращує соціальні умови. Особлива увага приділяється ролі менеджмент стандартам, таких як ISO 9001 [1], ISO 14001 [2], ISO 45001 [3], в забезпеченні ефективності, прозорості та стійкості в різних галузях. У дослідженні використані методи емпіричного аналізу, порівняння, аналізу та синтезу, індукції й дедукції, моделювання, а також спеціальні методи, такі як нормалізація даних, статистичний аналіз та візуалізація даних. Висвітлюються приклади успішного впровадження цифрових технологій у різних країнах та регіонах, які демонструють значний прогрес у досягненні ЦСР. Крім того, стаття надає рекомендації щодо подальшого використання цифрових технологій для підтримки сталого розвитку, враховуючи поточні виклики та можливості. Таким чином, дослідження показує, що цифрова трансформація не лише сприяє економічному розвитку, але й може стати потужним інструментом для забезпечення екологічної та соціальної стійкості.

Digital transformation has become an integral part of modern society, profoundly impacting all aspects of life: economic, social, and environmental. This article explores the relationship between sustainable development goals (SDGs) and quality standards during the digital transformation of business processes in IT companies. The article delves into the crucial intersection of quality standards and SDGs in the context of digital transformation within IT companies. As digital transformation becomes increasingly central to modern society, it significantly influences economic growth, social development, and environmental sustainability. This study examines how integrating quality standards such as ISO 9001 [1], ISO 14001 [2], and ISO 45001 [3], alongside cutting-edge digital technologies like the Internet of Things (IoT), blockchain, artificial intelligence (AI), and cloud computing, can enhance business processes. These technologies and standards not only drive economic growth but also reduce environmental impact and improve social conditions. The research utilizes a diverse range of methodological approaches, including empirical analysis, comparative studies, synthesis, induction, deduction, and modeling. Additionally, specialized techniques such as data normalization, statistical analysis, and data visualization are employed to provide a comprehensive understanding of the impacts of digital transformation. The article offers strategic recommendations for IT companies seeking to leverage digital technologies for sustainable development. These recommendations consider the current challenges and opportunities in the rapidly evolving digital landscape, stressing the importance of aligning digital transformation initiatives with quality standards and SDGs. In conclusion, this research highlights the dual role of digital transformation in promoting economic development and supporting environmental and social sustainability. It advocates for the harmonious integration of quality standards with SDGs to maximize the benefits of digital transformation in IT companies. The insights provided in this article are invaluable for researchers and practitioners aiming to navigate the complexities of digital transformation while promoting sustainable development. By aligning business processes with quality standards and SDGs, IT companies can not only enhance their operational efficiency and competitiveness but also make a positive contribution to global sustainability efforts.
Synergy of quality standards with sustainable development goals for managing the digital transformation of business processes in it companies
Keywords: цифрова трансформація; цілі сталого розвитку; стандарти якості; менеджмент; IT компанії; digital transformation; sustainable development goals; quality standards; management; IT companies